Evidence for Earlier Stone Age ‘coastal use’: The site of Dungo IV, Benguela Province, Angola - (:unkn) unknown (My University, 2023)
The relationship between Earlier Stone Age (ESA) hominins and the southern African coastal environment has been poorly investigated, despite the high concentration of openair sites in marine and fluvial terraces of the coastal plain from c. 1Ma onward during the Mid-Pleistocene Transition. Southern Africa provides some of the earliest evidence of coastal subsistence strategies since the end of the Middle Pleistocene, during the Middle Stone Age (MSA). These coastal MSA sites showcase the role of coastal environments in the emergence and development of modern human behaviors. Given the high prevalence of coastal ESA sites throughout the region, we seek to question the relationship between hominins and coastal landscapes much earlier in time. In this regard, the +100 m raised beaches of the Benguela Province, Angola, are key areas as they are well-preserved and contain a dense record of prehistoric occupation from the beginning of the Middle Pleistocene, including sites like Dungo, Mormolo, Sombreiro, Macaca and Punta das Vacas. Accordingly, this paper provides a critical review of the coastal ESA record of southern Africa and a detailed presentation of the Dungo IV site, through a qualitative technological analysis coupled with a quantitative inter-site comparison with contemporary southern African coastal plain sites. Through our detailed technological analyses, we highlight the influence of coastal lithological resources on the technical behaviors of hominin groups, and we propose the existence of a "regional adaptive strategy" in a coastal landscape more than 600 000 years ago. Finally, we argue for the integration of coastal landscapes into hominins' territories, suggesting that adaptation to coastal environments is actually a slower process which begins with "territorialization" well before the emergence and development of Homo sapiens.
Keywords: African Research